PREVALENCE OF GOATPOX DISEASE IN PUNJAB PROVINCE OF PAKISTAN - A. Sajid; Z. I. Chaudhary; U. Sadique; A. Maqbol; A. A. Anjum; Muhammad Subhan Qureshi; Z. U. Hassan; M. Idress; M. Shahid (Journal of Animal and Plant Sciences, 2012)
The present study was conducted to investigate the prevalence of pox infection in goats in Pakistan. The skin samples were collected from different locations of Northern, Arid and Southern regions of Punjab. From northern region, the total number of samples collected from slaughter houses, tanneries, goats and hide markets were 3438, 5038, 2841 and 4135 respectively. From arid regions the total samples number collected were 1873, 935, 3313 and 1110 respectively. Fromsouthern regions the total samples collected were 2243, 1758, 3745 and 1045 respectively. The prevalence of capripox virus was highest in arid region followed by southern region and northern regions. The data were analyzed by age and sex on the basis of clinical manifestation and postmortem lesions found in the infected animals. Prevalence was more in adults as compared to the kids. Female goats were more sensitive than male goats. The histopathological examination was performed and the characteristic changes were recorded. For goat pox the prevalence between the regions and samples collecting spots was highly significant (P<0.05).
Keywords: Goatpox; Histopathological changes; Postmortem Lesions; Punjab Province; Pakistan